Artificial Intelligence Simulation, Not Synthesis. - KASSAN, PETER (Skeptic, 2017)
The article discusses the possibility of artificial intelligence exceeding human intelligence. It notes that the field of artificial intelligence is simulating the synthesis of intelligence. It adds that confusion between simulation and synthesis is the root of a lot of muddled thinking. Brains evolved because they make animals better equipped to survive and reproduce in their ecological niches.